Analysis of Nutritional Substances and Acceptance of Tenggiri Fish Nugget Substitute of Moringa Leaf Flour as an Alternative for Preventing Anemia in Adolescent Women - Suaebah; Widyana Lakshmi Puspita; Jurianto Gambir; Yanuarti Petrika (POLTEKKES KEMENKES PONTIANAK, 2022)
In Indonesia, some plants contain many benefits for public health and contain very high nutrients ranging from macronutrients to micronutrients. These plants include Moringa oleifera L, the Moringa tree, by Indonesian people. However, few people know about the Moringa tree's benefits, so its utilization still needs to improve in society. This study was a pure experimental study consisting of 3 three treatments of mackerel fish nuggets with different substitutions for moringa leaf flour: P1=5, P2=12.5, P3=25. The third step was an organoleptic test at the Pontianak Ministry of Health's Poletkkes Food Technology Laboratory consisting of 25 panelists. Then proceed with nutritional analysis in the Chemistry laboratory at Tanjung Pura Pontianak University. The research design used a completely randomized design (CRD) data and was analyzed using the Freedman statistical test. The results of the study are based on Friedman's statistical test, which is enhanced with Conover with a 95% confidence level, showing that the results of T count > T table (13.6 > 3.175) mean that there is a color difference in the nugget formula, there is a difference in the aroma of the nugget formula with T count > F table (6.03 > 3.175) there is a difference in taste for variations in taste with T count < F table (2.72 < 3.175) Based on test results Laboratory tests on nuggets of moringa leaf flour substitution showed an average protein content of 7.08%, average moisture content of 2.01% average ash content of 5.15%.